1999
DOI: 10.1017/s0029665199001044
|View full text |Cite
|
Sign up to set email alerts
|

Diet selection and animal state: an integrative framework

Abstract: In the present paper we deal with the problems of explaining and predicting diet selection of animals under controlled conditions, i.e. conditions that can be described and in which any influences of the environment can be either controlled or at least monitored. Diet selection is considered within an integrative framework of feeding behaviour that views both food intake and diet selection as an outcome of the animal's internal state and knowledge of the feeding environment. Three questions that arise from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…Indeed, during this first challenge, the sheep ate all the concentrate offered for the first 2 days of this challenge and then refused half of it during the next 3 days. Kyriazakis et al (1999) suggested that animals adjust their dietary selection in response to a significant physiological change, which in our case could be an altered rumen state. Nevertheless, the decrease in wheat consumption over the following days did not allow a significant increase in ruminal pH at the end of challenge 1.…”
Section: Ruminal Phmentioning
confidence: 89%
“…Indeed, during this first challenge, the sheep ate all the concentrate offered for the first 2 days of this challenge and then refused half of it during the next 3 days. Kyriazakis et al (1999) suggested that animals adjust their dietary selection in response to a significant physiological change, which in our case could be an altered rumen state. Nevertheless, the decrease in wheat consumption over the following days did not allow a significant increase in ruminal pH at the end of challenge 1.…”
Section: Ruminal Phmentioning
confidence: 89%
“…Animal feeding behaviour has been described by Kyriazakis et al (1999) as a continuous close-looped system, whereby food intake and diet selection influence, and in turn are influenced by, an animal's internal state and knowledge of its feeding environment. The internal state changes as a direct consequence of feeding (or lack of it) or other stimuli.…”
Section: Human Evolutionary Perspectives On Eatingmentioning
confidence: 99%
“…hormone and metabolite levels or protein and lipid stores), but also externally based motivational aspects (e.g. perceived predation risk) [8][9][10]. Estimates of the motivational state could be derived from physiological measures like hormone profiles [8], or from behaviours that are specific for a certain context, e.g.…”
Section: Introductionmentioning
confidence: 99%